Analysis of factors related to the incidence of HIV/AIDS in adolescents aged 12-15 years at the Sorong Papua Community Health Center - Tuhumena, Femi Serly; Mainassy, Meillisa Carlen; Ruben, Sethiana Dewi; Suabey, Suningsih; Tandiola, Rosdiana; Tondok, Santalia Banne (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
HIV is a virus that attacks the human immune system and weakens our body's ability to fight all diseases that come. A dangerous disease caused by a virus that is transmitted through bodily fluids, especially due to sexual intercourse and injection drug use. Exposure to biological hazards can be caused by various means including ingestion, inoculation, bites, inhalation, through contact with skin abrasions and through blood splashes. The aim is to determine adolescent behavior and knowledge related to the incidence of HIV/AIDS in adolescents aged 12-15. This research is a quantitative research with a cross-sectional approach. In cross-sectional research, the researcher measures variables at a certain time on each subject who is only observed once and the subject variables are measured at the time of examination. Based on the results of research regarding the relationship between adolescent behavior and the incidence of HIV/AIDS in adolescents aged 12-15 years with objective criteria of being at risk and not being at risk, the result was that. From the results of data analysis using the chi-square statistical test, the value of p=0.486(α>0) was obtained. .05), this means Ha is accepted and Ho is rejected. Thus it can be said that there is a relationship between behavior.